2019
DOI: 10.9734/jammr/2019/v30i830224
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Regarding Infection Control Procedures among Dentists of Karachi

Abstract: Aim: Infection control is crucial in any clinical setting. It is vital that all dentists must follow the infection control protocols in their clinics to prevent cross-infection. In a dental clinic, even simple dental procedures including extractions, scaling and root planning, dental crown preparations and root canal treatment, have a high risk of exposure to blood, which may cause transmission bloodborne diseases. Dentist's compliance with these guidelines and recommendations have been recently studied in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
5
2
Order By: Relevance
“…In the present study, about 90% of the participants took history of communicable diseases prior to commencing treatment, which is similar to results of other studies reporting 92% and 89% of subjects taking pre-treatment disease history 12,13 . Around 75% subjects of this study asked patients for screening of communicable diseases which is far less as compared to a study by Hakam et al where 98% participants carried out routine screening of their patients before Prosthodontic procedures 5 .In our study, only 65.8% participants used disposable instruments in patients with communicable diseases which is an alarming number and needs to improve for better cross infection control measures.A study in Karachi reported compliance by 97.3 % of the subjects to isolate dental surfaces for preventing cross-infection.In contrast,only three-fourth of the participants of this study use plastic wrap for isolation of dental unit surfaces 14 .These results indicate that the measures taken to control cross-infection are below the level of standard care. Newer infection control practices and policies should be introduced like a cross-infection control administrator that will observe and keep an eye on infection control activities in health care centers.…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, about 90% of the participants took history of communicable diseases prior to commencing treatment, which is similar to results of other studies reporting 92% and 89% of subjects taking pre-treatment disease history 12,13 . Around 75% subjects of this study asked patients for screening of communicable diseases which is far less as compared to a study by Hakam et al where 98% participants carried out routine screening of their patients before Prosthodontic procedures 5 .In our study, only 65.8% participants used disposable instruments in patients with communicable diseases which is an alarming number and needs to improve for better cross infection control measures.A study in Karachi reported compliance by 97.3 % of the subjects to isolate dental surfaces for preventing cross-infection.In contrast,only three-fourth of the participants of this study use plastic wrap for isolation of dental unit surfaces 14 .These results indicate that the measures taken to control cross-infection are below the level of standard care. Newer infection control practices and policies should be introduced like a cross-infection control administrator that will observe and keep an eye on infection control activities in health care centers.…”
Section: Discussioncontrasting
confidence: 55%
“…A study carried out in Nepal showed that less than 50% of the subjects are aware about BMW management guidelines while on contrary, current study showed that 68.00% of subjects said that they are aware about the guidelines of BMW management [15] . A similar study conducted in Karachi, reported that 92.3% of the participants lacked knowledge regarding disposal of biomedical waste in different color coded bags, while on the other hand, current study showed that 53.00% of the subjects were totally incorrect and 30.00% of the subjects were partially correct regarding the disposal in color coded bags [16] . A study in Kuwait also showed poor practice with regards to SPs and BMW management of which only 27.7% reported correct practices which was almost similar to our study which revealed 20.00% of subjects reporting correct practices of BMW management and 37.00% of subjects reporting correct practices of SPs [17] .…”
Section: Discussioncontrasting
confidence: 43%
“…Multiple researches have concluded that dentists in Karachi have adequate knowledge of cross infection control protocols [17,18,19] . However, an aspect to consider here is that while the DHCPs participating in the study showed adequate knowledge and practice of general cross infection prevention protocols, their adaptation of the new mandatory updates in cross infection control, specifically targeted to limit Covid 19 spread was below satisfactory.…”
Section: Discussionmentioning
confidence: 99%